2019
DOI: 10.1139/cjpp-2018-0529
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against COPD by attenuating apoptosis and endoplasmic reticulum stress via upregulating SIRT1 expression in rats

Abstract: The apoptosis of bronchial and alveolar epithelial cells plays a key role in chronic obstructive pulmonary disease (COPD). The endoplasmic reticulum (ER) stress induced by cigarette smoke contributes to apoptosis. Previous studies demonstrated that melatonin prevented the development of COPD. In addition, silent information regulator 1 (SIRT1) had a protective effect against COPD. However, it remains unclear whether SIRT1 is involved in the protection of melatonin against COPD. In this study, 32 male Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Kelsen et al [ 24 ] reported that ER stress is activated by cigarette smoke in lung tissues of patients with COPD. He et al [ 25 ] reported that inhibiting ER stress exerted protective effects against COPD by inhibiting the apoptosis of bronchial and alveolar epithelial cells. Moreover, Zhao et al [ 26 ] found that ER stress played an important role in the apoptosis of alveolar epithelial apoptosis in COPD, and adiponectin can ameliorate the progression of COPD through inhibiting the ERS-induced alveolar epithelial apoptosis in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Kelsen et al [ 24 ] reported that ER stress is activated by cigarette smoke in lung tissues of patients with COPD. He et al [ 25 ] reported that inhibiting ER stress exerted protective effects against COPD by inhibiting the apoptosis of bronchial and alveolar epithelial cells. Moreover, Zhao et al [ 26 ] found that ER stress played an important role in the apoptosis of alveolar epithelial apoptosis in COPD, and adiponectin can ameliorate the progression of COPD through inhibiting the ERS-induced alveolar epithelial apoptosis in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Through its antioxidant and anti-inflammatory effects, melatonin is beneficial in pulmonary hypertension [ 203 , 204 , 205 ], enhances the NO-independent acetylcholine’s vasodilatory effect, decreases the systolic pressure of the right ventricle, and prevents right ventricular hypertrophy [ 206 ]. By diminishing TGF-β1 activity, apoptosis, and endoplasmic reticulum stress via Sirtuin-1 upregulation in animal studies, melatonin could be protective in chronic obstructive pulmonary disease (COPD) [ 72 , 207 ]. It also decreases dyspnea and 8-isoprostane in the exhaled air, in humans [ 208 ].…”
Section: Melatonin As An Adjuvant In Respiratory Distress Caused Bmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is a lung disease associated with chronic airway inflammation, which limits the airflow in the lungs. The underlying mechanisms responsible for the development of COPD involve inflammation, apoptosis, and airway epithelial remodeling [ [91] , [92] , [93] ]. It was reported that 80 % of lung cancer patients suffer from COPD [ 94 ].…”
Section: Copdmentioning
confidence: 99%